The effects of anthropometric and demographic factors on conduction parameters of the ulnar nerve: Multivariate analysis. (24th August 2020) - Mondelli, Mauro; Vinciguerra, Claudia; Aretini, Alessandro; Ginanneschi, Federica
Highlights: Age correlate with all sensory and motor ulnar nerve parameters. Cubital groove and elbow anthropometry are not related to ulnar conduction. Effects of anthropometric and demographic data vary depending on conduction parameter. The cut-offs to diagnose ulnar neuropathy at the elbow should be revised. Abstract: The objective of the study is to investigate the effects of age, height, gender, body mass index (BMI), waist-to-hip ratio (WHR), arm and elbow measures on ulnar nerve conduction. We enrolled 261 "disease-free" subjects. We analyzed motor conduction velocity (MCV) in across elbow (AE) and forearm tracts, and sensory conduction velocity in 4th, 5th digit-wrist tracts (U4, U5) and in dorsal ulnar cutaneous nerve (DUC). We calculated the amplitudes of sensory and motor potentials (CMAPa and SNAPa), % of CMAPa drop AE, MCV drop and distal motor latency (DML). Univariate and multivariate analyses were performed. We estimated the predictive equations. The median nerve was examined for comparison. Age was negatively correlated with all conduction parameters. Forearm and AE MCV, % of CMAPa drop, DML, U4 and U5 SCV also depended upon height. Females had higher U4 and U5 SNAPa than males. BMI showed inverse relationship with U4 and U5 SNAPa. DUC parameters depended upon BMI and arm length. Similar trends were observed for the median nerve. "Normative" ulnar conduction parameters should be adjusted for demographic and anthropometric measures to improve diagnostic sensitivity.